Teachers and Leaders in Vocational Education and Training - (:unkn) unknown (OECD Publishing, 2021)
"Vocational education and training (VET) plays a central role in preparing young people for work, developing the skills of adults and responding to the labour market needs of the economy. Teachers and leaders in VET can have an immediate and positive influence on learners' skills, employability and career development. However, when compared to general academic programmes, there is limited evidence on the characteristics of teachers and institutional leaders in VET and the policies and practices of attracting and preparing them. VET teachers require a mix of pedagogical skills and occupational knowledge and experience, and need to keep these up to date to reflect changing skill needs in the labour market and evolving teaching and learning environments. This report fills the knowledge gap on teachers and leaders in VET, and produces new insights into what strategies and policies can help develop and maintain a well prepared workforce. It zooms in on VET teacher shortages; strategies for attracting and retaining teachers; initial training and professional development opportunities for teachers; the use of innovative technologies and pedagogical strategies; and the important role of institutional leaders and strategies for better preparing and supporting them." (Editor; BIBB-Doku)
Keywords: P 3.2.3 Lehrer; G 1.2.3.2 Anforderungen & Bedarfe; Berufsbildung; Berufsschullehrer; Attraktivität; Fachkräftebedarf; Kompetenzentwicklung; Digitalkompetenz; Lehrerausbildung; OECD-Staaten